PSYCHOLOGICAL FEATURES OF IMAGE DEVELOPMENT FUTURE PRACTICAL PSYCHOLOGISTS - Хоменко-Семенова, Леся; Дарійчук, О. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article deals with the problem of psychological features of the development the image future practical psychologists. Theoretical approaches to understanding the concept of image analised, its role in the structure of the profession of a practical psychologist is presented. Much attention is paid to comparing the definition of the concept of image in terms of synonymous, classification, functional, communicative, projective approaches. The psychological features that underlie the development of the image future practical psychologists, such as communicative abilities, level of self-realization are considered. Also, the importance of building a professional image and using it to be a competitive professional and a topical specialist in the labor market is substantiated. The article describes the results of the empirical study of the level of communication, the level of self-realization and level of self-confidence from students of the direction "Practical psychology", for which was initiated the diagnostics of the level of communicative abilities by the method of V.V. Sinyavsky and B.O. Fedoryshyn, the level of self-realization of personality by the method of S.I. Kudinov and the level of self-esteem by the method of Dembo-Rubinstein. The results obtained indicate that practical psychologists have high level of communicative abilities, harmonious level of self-realization, mainly high and medium level of self-esteem of dominant individual-psychological characteristics: communicative abilities, self-esteem, self-realization . The article presents the analysis of psychological features of forming the image of practical psychologists from the point of view of psychological substantiation of the level of their formation and concludes the prevailing level